2020
DOI: 10.1101/2020.09.24.312595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-affinity RBD-targeting nanobody improves fusion partner’s potency against SARS-CoV-2

Abstract: A key step to the SARS-CoV-2 infection is the attachment of its Spike receptor-binding domain (S RBD) to the host receptor ACE2. Considerable research have been devoted to the development of neutralizing antibodies, including llama-derived single-chain nanobodies, to target the receptor-binding motif (RBM) and to block ACE2-RBD binding. Simple and effective strategies to increase potency are desirable for such studies when antibodies are only modestly effective. Here, we identify and characterize a high-affini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The cryo-EM structure suggested Sb23 as a Class 2 indicating that interacts with the S protein, wherein two RBDs are in the “up” conformation [ 250 ]. SR31, another Sb isolated from a synthetic library, interacts with the RBD, distorting it, and does not neutralize SARS-CoV-2 pseudovirus [ 251 ]. Since SR31 displays high affinity, its fusion with other neutralizing Sbs, such as SR31-MR17 or SR31-MR6, increases the neutralization activity against SARS-CoV-2 pseudovirus (IC 50 : 52.8 µg/mL or 2.7 µg/mL, respectively) [ 251 ].…”
Section: Insights From Ab Therapeutic Strategies Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…The cryo-EM structure suggested Sb23 as a Class 2 indicating that interacts with the S protein, wherein two RBDs are in the “up” conformation [ 250 ]. SR31, another Sb isolated from a synthetic library, interacts with the RBD, distorting it, and does not neutralize SARS-CoV-2 pseudovirus [ 251 ]. Since SR31 displays high affinity, its fusion with other neutralizing Sbs, such as SR31-MR17 or SR31-MR6, increases the neutralization activity against SARS-CoV-2 pseudovirus (IC 50 : 52.8 µg/mL or 2.7 µg/mL, respectively) [ 251 ].…”
Section: Insights From Ab Therapeutic Strategies Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…In this study, we report two high-affinity RBD binders isolated from immunized alpaca and their structural and biological characterization. Most monovalent RBDtargeting nanobodies bind S or RBD with KD in the nanomolar ranges [9][10][11][12][13][14][15][16][17][18]21 .…”
Section: Discussionmentioning
confidence: 99%
“…Being small, nanobodies are ultra-stable, relatively easy to produce (in microbial) with low costs and high yields, and amenable to protein engineering such as fusion in various forms. Such fusion can result in improved potency -binding affinity and neutralizing activity can increase by hundreds to thousands of fold [9][10][11] . In addition, nanobodies that recognize non-competing epitopes can be conveniently fused to make biparatopic nanobodies that are potentially more tolerant to escape mutant strains 9,10,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last one (Sb23) can also bind the RBD in both "up" and "down" conformation (Custodio et al 2020). Also, Yao et al (2020) identified a new synthetic Nb. Selected sybody (named SR31) displayed poor neutralization activity against SARS-CoV-2 pseudo-virus.…”
Section: Neutralizing Vhh Against Viral Zoonosismentioning
confidence: 99%